Promoting social change and democracy through information technology - Kumar, Vikas, 1979-; Svensson, Jakob (A volume in the Advances in Electronic Government, Digital Divide, and Regional Development (AEGDDRD) Book Series, 2015)
"This book is a definitive reference source for the latest scholarly research on the use of the internet, mobile phones, and other digital platforms for political discourse between citizens and governments"--